Implementasi Trilogi Pemberdayaan Masyarakat bagi Kelompok Peternak Domba/Kambing di Desa Gorowong, Parung Panjang, Bogor - Abidin, Zainal; Mais, Rimi Gusliana; Adawiyah, Wiwiek Rabiatul (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2024)
This study examines the implementation of a community empowerment trilogy aimed at increasing economic self-reliance among sheep and goat farmers in Gorowong Village. The main challenges these farmers face include limited access to capital, low management skills, and dependency on intermediaries. This program implements three empowerment components: capital support, capacity building for farmers, and purchase guarantees. The implementation methods include stages of socialization, training, technology application for grazing management, ongoing mentorship, and evaluation, all designed to build capacity and optimize land use for grazing. Initial results show improvements in farmers’ technical skills, community engagement in sustainable management practices, and significant income growth. The program has reduced farmers’ reliance on intermediaries and strengthened financial independence through financial literacy skills. To ensure sustainability, this article recommends further support in marketing, continuous training, and access to low-interest financing. This research contributes to the literature on agricultural-based community empowerment by providing a replicable model for sustainable economic growth in rural communities.